The impact of the 2030 Climate and Energy Framework Agreement on electricity prices in MIBEL: A mixed-methods approach - Estevão, João (2018)
European Union member countries signed the 2030 Climate and Energy Framework Agreement on October 24, 2014. This framework brings with it changes in the expectations of energy consumers and producers, which opens new avenues of research. This study examines and compares the behavior of spot electricity prices in the Iberian market, MIBEL, before and after the 2030 Agreement. We adopt a mixed-methods approach that combines a more traditional GARCH model with the qualitative fsQCA. The GARCH accounts for the well-documented characteristics of electricity prices: seasonality, high volatility, and price peaks. This method generates evidence from the Spanish and Portuguese data of reduced volatility and higher stability in prices after the signing of the 2030 Agreement. The fsQCA supports these results by identifying a larger number of paths that lead to price stability for the sub period after the signing of the 2030 Agreement.